2022
DOI: 10.1101/2022.06.03.22275891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A More Accurate Measurement of COVID-19 Hospitalizations

Abstract: COVID-19 hospitalizations are a key indicator of the SARS-CoV-2 pandemic. The US Centers for Disease Prevention and Control describes oxygen supplementation as a measure of severe disease. SARS-CoV-2 PCR positive patients hospitalized without hypoxia or requiring oxygen may have been identified incidentally due to routine screening practices. We describe the application of a revised case definition for COVID-19 hospitalization based on the case-patient oxygen requirement on admission. Using data collected fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…COVID-19 testing capacity and capability have changed rapidly throughout the course of the pandemic, and COVID-19 laboratory testing results were not widely available in the databases utilized for this study, so COVID-19 diagnoses rather than confirmed COVID-19 infections were used as outcomes. COVID-19 severity is not accurately represented in diagnoses, 38 so we evaluated COVID-19 diagnoses overall in any medically attended setting, and separately in hospital/ED settings as a proxy for severity. However, as the pandemic has progressed, COVID-19-related hospitalizations may be the most relevant public health measure for contemporary surveillance and prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 testing capacity and capability have changed rapidly throughout the course of the pandemic, and COVID-19 laboratory testing results were not widely available in the databases utilized for this study, so COVID-19 diagnoses rather than confirmed COVID-19 infections were used as outcomes. COVID-19 severity is not accurately represented in diagnoses, 38 so we evaluated COVID-19 diagnoses overall in any medically attended setting, and separately in hospital/ED settings as a proxy for severity. However, as the pandemic has progressed, COVID-19-related hospitalizations may be the most relevant public health measure for contemporary surveillance and prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the pandemic has progressed, COVID-19-related hospitalizations may be the most relevant public health measure for contemporary surveillance and prevention efforts. 38,39 We matched vaccination groups on calendar time and evaluated outcomes over calendar time to account for the potentially changing meaning of a COVID-19 diagnosis over time (e.g., care seeking for COVID-19 versus incidental findings).…”
Section: Discussionmentioning
confidence: 99%